Relationship Between Psychological Distress, Burnout and Work Engagement in Workers During the COVID-19 Pandemic: A Systematic Review - Ingrid Adanaqué-Bravo; Kenny Escobar-Segovia; Juan Gómez-Salgado; Juan Gómez-Salgado; Juan Jesús García-Iglesias; Javier Fagundo-Rivera; Carlos Ruiz-Frutos; Carlos Ruiz-Frutos (International Journal of Public Health, 2023)
Objective: The psychological distress that the COVID-19 pandemic has produced has generated negative effects on workers, and in one way or another this has affected their work engagement within companies. The aim of this research was to assess the relationship between psychological distress, burnout and work engagement in workers during the COVID-19 pandemic.Methods: A systematic review was carried out following the PRISMA methodology, taking articles from the Scopus, Pubmed, and Web of Science databases from the beginning of the pandemic until November 2022. The methodological quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools for non-randomised studies.Results: 24 articles were selected. All the articles found an association between psychological distress, burnout or other factors and work engagement.Conclusion: The COVID-19 pandemic has had an impact on work engagement and a negative relationship with psychological distress and burnout, hence the importance of companies taking measures to minimise levels of psychological distress and burnout.